Improvement of renal function after transcatheter aortic valve replacement and its impact on survival - Kylies, Dominik; Freitag-Wolf, Sandra; Fulisch, Florian; Seoudy, Hatim; Kuhn, Christian; Kihm, Lars Philipp; Pühler, Thomas; Lutter, Georg; Dempfle, Astrid; Frey, Norbert; Feldkamp, Thorsten; Frank, Derk (BMC nephrology, 2021)
Background: Chronic kidney disease as well as acute kidney injury are associated with adverse outcomes after transcatheter aortic valve replacement (TAVR). However, little is known about the prognostic implications of an improvement in renal function after TAVR. Methods: Renal improvement (RI) was defined as a decrease in postprocedural creatinine in μmol/l of ≥1% compared to its preprocedural baseline value. A propensity score representing the likelihood of RI was calculated to define patient groups which were comparable regarding potential confounders (age, sex, BMI, NYHA classification, STS score, log. EuroSCORE, history of atrial fibrillation/atrial flutter, pulmonary disease, previous stroke, CRP, creatinine, hsTNT and NT-proBNP). The cohort was stratified into 5 quintiles according to this propensity score and the survival time after TAVR was compared within each subgroup. Results: Patients in quintile 5 (n = 93) had the highest likelihood for RI. They were characterized by higher creatinine, lower eGFR, higher NYHA class, higher NT-proBNP, being mostly female and having shorter overall survival time. Within quintile 5, patients without RI had significantly shorter survival compared to patients with RI (p = 0.002, HR = 0.32, 95% CI = [0.15–0.69]). There was no survival time difference between patients with and without RI in the whole cohort (p = 0.12) and in quintiles 1 to 4 (all p > 0.16). Analyses of specific subgroups showed that among patients with NYHA class IV, those with RI also had a significant survival time benefit (p < 0.001, HR = 0.15; 95%-CI = [0.05–0.44]) compared to patients without RI. Conclusions: We here describe a propensity score-derived specific subgroup of patients in which RI after TAVR correlated with a significant survival benefit
Gesehen am 31.08.2021